2017
DOI: 10.1002/jcb.26350
|View full text |Cite
|
Sign up to set email alerts
|

P2Y6 regulates cytoskeleton reorganization and cell migration of C2C12 myoblasts via ROCK pathway

Abstract: Migration of skeletal muscle precursor cells is required for limb muscle development and skeletal muscle repair. This study aimed to examine the role of P2Y6 receptor in C2C12 myoblasts migration. C2C12 myoblasts were treated with P2Y6 agonist UDP, P2Y6 antagonist MRS2578, Ca channel blocker BTP2, or ROCK inhibitor GSK269962 or Y27632, and the migration ability of C2C12 cells was assessed by wound healing assay. The cellular Ca content was analyzed with fluo-4 probe and the activation of ROCK (phosphorlyation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…Values were expressed as the mean ± SEM from three to four independent experiments performed in duplicate. Statistical significance was determined by a two-way ANOVA test with multiple comparisons followed by a Tukey posttest myoblasts (Wang et al, 2018). Here, we inhibited ROCK activity using 1 μM Y-27632 before the stimulation of P2Y 6 with 5 μM MRS2693 (Figure 3).…”
Section: The Pro-migratory Effect Of P2y 6 On A549 Cells Requires Amentioning
confidence: 99%
See 1 more Smart Citation
“…Values were expressed as the mean ± SEM from three to four independent experiments performed in duplicate. Statistical significance was determined by a two-way ANOVA test with multiple comparisons followed by a Tukey posttest myoblasts (Wang et al, 2018). Here, we inhibited ROCK activity using 1 μM Y-27632 before the stimulation of P2Y 6 with 5 μM MRS2693 (Figure 3).…”
Section: The Pro-migratory Effect Of P2y 6 On A549 Cells Requires Amentioning
confidence: 99%
“…These messengers modulate the activity of different effectors, such as protein kinases C (PKC) and MAP kinases (Bellefeuille, Molle, & Gendron, 2019). Recently, it was reported that P2Y 6 stimulated the Rho-associated protein kinase (ROCK) pathway to favor the migration of C2C12 myoblasts through the reorganization of the cytoskeleton following the phosphorylation of LIM kinases (LIMK) and cofilin (Wang et al, 2018). Interestingly, the modulation of C2C12 migration was not associated with any G-protein activity, although a previous study reported the potential association of P2Y 6 to Gα 12/13 proteins in cardiomyocytes (Nishida et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Proliferation and migration of myoblasts are essential for muscle development, as they facilitate cellular alignment in preparation for differentiation and fusion ( Wang et al, 2018 ). CNN3 plays a pivotal role in promoting the migration of cancer cells, skin cells, and trophoblast invasion ( Shibukawa et al, 2010 ; Daimon et al, 2013 ; Kim et al, 2018 ; Nair et al, 2019 ; Xia et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Co lin also acts downstream of RhoA to regulate actin dynamics that may affect muscle cell migration and regeneration. The C2C12 myoblast migration is regulated by RhoA/ROCK signaling pathway where Co lin levels and activity is important 59 . Increased phosphorylation of Co lin inhibits its actin severing activity.…”
Section: Discussionmentioning
confidence: 99%